Oblicz równanie:

12 - x/4 * 12 - x/4 = x + 4/12 * x +4/12


Odpowiedź :

Cześć!

Odpowiedź: w załączniku

Szczegółowe wyjaśnienie

Zobacz obrazek MertB

Odpowiedź:

12 - x/4 * 12 - x/4 = x + 4/12 * x +4/12

12 - 3x - 1/4x=x+1/3x+1/3

- 3x - 1/4x - x - 1/3x=1/3 - 12

- 4x - 3/12x - 4/12x= - 11 2/3

- 4 7/12x= - 11 2/3

- 55/12x= - 35/3 /*( - 12/55)

x=140/55=28/11=2 6/11

spr

12 - 28/11*1/4*12 - 28/11*1/4=28/11+4/12*28/11+4/12

12 - 84/11 - 7/11=28/11+28/33+11/33

12 - 91/11=28/11+39/33

132/11 - 91/11=28/11+13/11

41/11=41/11

Szczegółowe wyjaśnienie: